PERSEPSI TOKOH LINTAS AGAMA KABUPATEN PROBOLINGGO TERHADAP PERPPU NOMOR 2 TAHUN 2017 TENTANG HAK BERSERIKAT - M Saiful Anam; Abd Rozaq (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2019)
Rights are the power to accept or do something that should be accepted or carried out by certain parties and can be prosecuted forcibly. There are two basic types of human rights, equality rights such as the right to be treated equally and the right to freedom such as freedom to worship, freedom to hold opinions, freedom of association, etc. Many pro-contra in society toward Government Regulation Act No. 2 of 2017 on the right of association. Suspicion from some communities that the motives or intentions of the Act are actually more aimed at Islamic-based community organizations than others. This applied research type is a form of descriptive research that describes a review of problems in society. In this study, the researchers reviewed the opinions of interfaith leaders on the right to organize in Act No. 2 of 2017. The results of this study are: 1) the perception of the Islamic community leaders in the Probolinggo district, is to support the changes in the act of community organizations. This is due to several legal reasons related to the emergency conditions that occurred. In addition, the right to organize in Islam needs to be regulated. God regulates and gives a measure of the right to associate. Not absolutely free. 2) Whereas according to Christian leaders, associate rights are social rights. Social rights are useful for maintaining and facilitating the achievement of personal rights. So the association right is free to use if it is not in its orientation, namely ensuring the fulfilment of personal rights such as speaking, living happily, etc. So automatically the right of association should not be fought if it is contrary to personal rights. This has become the basis for an agreement with Act No. 2 of 2017 agreed to be formalized.